2016
DOI: 10.1088/0957-4484/27/10/105202
|View full text |Cite
|
Sign up to set email alerts
|

Eu-doped ZnO–HfO2hybrid nanocrystal-embedded low-loss glass-ceramic waveguides

Abstract: We report on the sol-gel fabrication, using a dip-coating technique, of low-loss Eu-doped 70SiO2 -[Formula: see text] HfO2-xZnO (x = 2, 5, 7 and 10 mol%) ternary glass-ceramic planar waveguides. Transmission electron microscopy and grazing incident x-ray diffraction experiments confirm the controlled growth of hybrid nanocrystals with an average size of 3 nm-25 nm, composed of ZnO encapsulated by a thin layer of nanocrystalline HfO2, with an increase of ZnO concentration from x = 2 mol% to 10 mol%  in the SiO2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…These molecules are volatile and seen as a white smoke during the fast decomposition, and they may be readsorbed on the sponge surface if the gas flow is not high enough or the powder bed is too thick to transport these product molecules away. No peak was found around 407 eV, where the N 1s peak of N 5+ in nitrate is expected, which shows that no nitrate remained after the fast reaction. , The amount of carbon and nitrogen was low, while the amount of oxygen per metal (Table ) was much higher than that in the samples made at higher temperatures. This fits the IR and TG data, which showed that there were a few percent of residues, probably mainly as carboxylates, such as unreacted OAc groups left at 200 °C, which increases the oxygen to metal content.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…These molecules are volatile and seen as a white smoke during the fast decomposition, and they may be readsorbed on the sponge surface if the gas flow is not high enough or the powder bed is too thick to transport these product molecules away. No peak was found around 407 eV, where the N 1s peak of N 5+ in nitrate is expected, which shows that no nitrate remained after the fast reaction. , The amount of carbon and nitrogen was low, while the amount of oxygen per metal (Table ) was much higher than that in the samples made at higher temperatures. This fits the IR and TG data, which showed that there were a few percent of residues, probably mainly as carboxylates, such as unreacted OAc groups left at 200 °C, which increases the oxygen to metal content.…”
Section: Resultsmentioning
confidence: 85%
“…No peak was found around 407 eV, where the N 1s peak of N 5+ in nitrate is expected, which shows that no nitrate remained after the fast reaction. 130,131 The amount of carbon and nitrogen was low, while the amount of oxygen per metal (Table 1) was much higher than that in the samples made at higher temperatures. This fits the IR and TG data, which showed that there were a few percent of residues, probably mainly as carboxylates, such as unreacted OAc groups left at 200 °C, which increases the oxygen to metal content.…”
Section: Resultsmentioning
confidence: 91%
“…Shivakiran et al demonstratedp lanar waveguidesf rom Eu-doped SiO 2 -HfO 2 -ZnO ternary glass-ceramics. [18] Chen and Yins uccessfully precipitated sodium lanthanide fluorides NaLnF 4 (Ln = La-Lu) with cubic and hexagonal phase in aluminosilicate glass and demonstrate random upconversion lasing in the Yb/Er:b-NaYF 4 embedded glass-ceramics. [19] In 2016, Xu and Yu et al realized high-performancea nd compact self-cooling lasers for high temperature operation by using Ba 2 LaF 7 :Yb/ Er embedded glass-ceramics ( Figure 3).…”
Section: Lanthanide-doped Amorphous Materialsmentioning
confidence: 99%
“…Shivakiran et al. demonstrated planar waveguides from Eu‐doped SiO 2 ‐HfO 2 ‐ZnO ternary glass‐ceramics . Chen and Yin successfully precipitated sodium lanthanide fluorides NaLnF 4 (Ln=La‐Lu) with cubic and hexagonal phase in aluminosilicate glass and demonstrate random upconversion lasing in the Yb/Er:β‐NaYF 4 embedded glass‐ceramics .…”
Section: Lanthanide‐doped Amorphous Materialsmentioning
confidence: 99%
“…Silica-hafnia glass waveguides prepared by sol-gel method are reported as low-loss waveguides and it transforms into glass-ceramic waveguides due to the formation of HfO 2 nanocrystals within the glass matrix after performing an additional heat-treatment at 1000 • C [13,14]. On the other hand, SiO 2 -ZnO composite glass-ceramic waveguides [15] also attract attention for photonic applications due to high nonlinear optical properties of ZnO and also due to the attractive properties of ZnO as a direct band gap semiconductor having wide band gap of ∼3.37 eV as well as large exciton binding energy of 60 meV at room temperature [16][17][18].…”
Section: Introductionmentioning
confidence: 99%